Angelina and Henry - Holabird, Katharine; Craig, Helen (Middleton, Wis. : Pleasant Co. Publications, 2002)
While on a camping trip with Uncle Louie, two young mice named Angelina and Henry become lost in the woods until the "fit and fearless" Angelina saves the day.
"Ages 3 and up"-- Jacket
Accelerated Reader AR
Keywords: Mice -- Fiction; Camping -- Fiction; Uncles -- Fiction; Courage -- Fiction; Lost children -- Fiction